(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper explores the evolving legal landscape of sexual health in the United States, focusing on contraception and HIV prevention. It examines how legal tools – through regulation, litigation, and executive action – have been strategically used to restrict access to care. Tracing comparisons between challenges to the Affordable Care Act’s Contraceptive and PrEP mandates, the analysis situates these conflicts within broader cultural, ideological, and economic battles over public health, federalism, bodily autonomy, and equality, culminating in a legal moment where sexual health is not merely debated but weaponized.